Supplier Selection Using Analytical Hierarchy Process at PT. Indolakto - Putri Candra Anggani; Imam Baihaqi (Jurnal Sains dan Seni ITS, 2017)
Dairy supply chain is one of food supply chain that has its own uncertainty both in upstream and downstream process due to the durability of product. Dairy market has good demand trend, because the supply is still below the consumption level. Indonesia use imported dairy product rather than use the domestic ones, because the supply of domestic dairy still below the demand. So, there are opportunities for dairy company to compete in this industry and reach competitive advantage by solving the upstream problems. Selecting supplier is one of upstream supply chain area which affected the quality of dairy product and mitigate supply chain risk management from the beginning. This research aim to develop a framework for supplier selection. According to AHP method this research will be determine main criteria by interview, pair wise comparison on developing the AHP, determine sub criteria based on main criteria, and rank the supplier. The result is forming a framework of supplier selection based on company requirements. Also, the main criteria for supplier selection are quality, quantity, delivery, warranty, and pricing with sub main criteria which already deployed. Maltodextrin A will be choose rather than Maltodextrin B. The sensivity analysis also shown that all of criteria were robust.